2020
DOI: 10.1186/s13756-020-00844-0
|View full text |Cite
|
Sign up to set email alerts
|

Disinfectant wipes transfer Clostridioides difficile spores from contaminated surfaces to uncontaminated surfaces during the disinfection process

Abstract: Background Pre-wetted disinfectant wipes are increasingly being used in healthcare facilities to help address the risk of healthcare associated infections (HAIs). However, HAIs are still a major problem in the US with Clostridioides difficile being the most common cause, leading to approximately 12,800 deaths annually in the US. An underexplored risk when using disinfectant wipes is that they may cross-contaminate uncontaminated surfaces during the wiping process. The objective of this study was to determine t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…Despite product contamination, as demonstrated by Serratia marcescens and Achromobacter xylosoxidans presence in a quaternary ammonium disinfectant and its cleaned surfaces (58), the cleaning process should also be effective and standardized. Other studies demonstrated carryover contamination by cleaning wipes when the process is not well established (59) and when there is a greater compliance in the cleaning process by healthcare workers, it was possible to drastically reduce HAI caused by C difficile, MRSA, and VRE (60). The presence of nosocomial pathogens in some sanitizer samples raises concerns about their effectiveness in controlling bacterial growth, and the detection of antimicrobial resistance genes in sanitizer samples further emphasizes the importance of assessing the efficacy of sanitization protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Despite product contamination, as demonstrated by Serratia marcescens and Achromobacter xylosoxidans presence in a quaternary ammonium disinfectant and its cleaned surfaces (58), the cleaning process should also be effective and standardized. Other studies demonstrated carryover contamination by cleaning wipes when the process is not well established (59) and when there is a greater compliance in the cleaning process by healthcare workers, it was possible to drastically reduce HAI caused by C difficile, MRSA, and VRE (60). The presence of nosocomial pathogens in some sanitizer samples raises concerns about their effectiveness in controlling bacterial growth, and the detection of antimicrobial resistance genes in sanitizer samples further emphasizes the importance of assessing the efficacy of sanitization protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Despite product contamination, as demonstrated by Serratia marcescens and Achromobacter xylosoxidans presence in a quaternary ammonium disinfectant and its cleaned surfaces ( 59 ), the cleaning process should also be effective and standardized. Other studies demonstrated carryover contamination by cleaning wipes when the process is not well established ( 60 ) and when there is a greater compliance in the cleaning process by healthcare workers, it was possible to drastically reduce HAI caused by C. difficile, MRSA, and VRE ( 61 ). The presence of nosocomial pathogens in some sanitizer samples raises concerns about their effectiveness in controlling bacterial growth, and the detection of antimicrobial resistance genes in sanitizer samples further emphasizes the importance of assessing the efficacy of sanitization protocols.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the surface of the object would not be damaged; it has the ability of fast sterilization, and exhibits no corrosivity and toxicity; it does not need cleaning treatment before and after disinfection; it has the effect of cleaning and disinfection; the residual ammonium salt components possess antibacterial ability, which contribute to avoid cross pollution and significantly improve the compliance. Studies (Nkemngong et al, 2020) indicated that the positive rate of bacteria decreased after disinfection when wipes containing quaternary ammonium disinfectants were employed to wipe and disinfect the surface of the objects. It was also found that nurses of 65 ICUs disinfected mechanical prevention devices before use (52.0%), 118 ICUs after use (94.4%) and 65 ICUs before and after use (52.0%).…”
Section: Discussionmentioning
confidence: 99%